2020
DOI: 10.1186/s13195-020-00588-4
|View full text |Cite
|
Sign up to set email alerts
|

The clinical promise of biomarkers of synapse damage or loss in Alzheimer’s disease

Abstract: Background: Synapse damage and loss are fundamental to the pathophysiology of Alzheimer's disease (AD) and lead to reduced cognitive function. The goal of this review is to address the challenges of forging new clinical development approaches for AD therapeutics that can demonstrate reduction of synapse damage or loss. The key points of this review include the following: Synapse loss is a downstream effect of amyloidosis, tauopathy, inflammation, and other mechanisms occurring in AD. Synapse loss correlates mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 216 publications
(186 citation statements)
references
References 162 publications
4
162
2
1
Order By: Relevance
“…In our assessment of disease biomarkers, we focused on a small set of markers with the best-established association with the prion disease process. Future analyses could explore other emerging biomarkers of neurodegeneration, such as synaptic proteins [69,70]. Table 2 Comparison of visits for one RT-QuIC-positive study participant.…”
Section: Discussionmentioning
confidence: 99%
“…In our assessment of disease biomarkers, we focused on a small set of markers with the best-established association with the prion disease process. Future analyses could explore other emerging biomarkers of neurodegeneration, such as synaptic proteins [69,70]. Table 2 Comparison of visits for one RT-QuIC-positive study participant.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies identified the oligomeric forms of Aβ and tau, rather than larger aggregates, to be the synaptotoxic species. 45 - 49 Both in vivo 50 and ex vivo 51 Aβ oligomers (Aβo) disrupt LTP, probably interfering with NMDAR ( N -methyl- d -aspartate receptor) activity and downstream pathways, 52 in addition to causing oxidative stress, impairing axonal transport, and causing nerve cell death (reviewed in Cline et al 53 ). In AD, Aβ and tau act in concert and studies have identified their simultaneous presence in the postsynaptic compartment.…”
Section: Pathophysiology Of Synaptic Dysfunction and Lossmentioning
confidence: 99%
“…The presence of amyloid beta oligomer (AβO) has been correlated with synaptic plasticity impairment and frank synapse loss in mice and cell models [20][21][22][23] and in human brains in AD [24,25]. The cognitive impairment in AD closely parallels the loss of synapses due to the toxic effects of Aβ, tau, and inflammation; thus, emerging biomarkers are able to measure synapse injury and loss in the brain and may correlate with cognitive function in AD [26].…”
Section: Biomarkers In Alzheimer's Diseasementioning
confidence: 99%